2009
DOI: 10.1007/s12039-009-0117-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies and antimicrobial properties of norcembrane diterpenoid from an Indian soft coral Sinularia inelegans Tixier-Durivault

Abstract: Two metabolites featuring norcembranoid diterpene skeleton have been isolated from chloroform extract of soft coral of the genus sinularia, which was collected from the southern coast of India. The structures of the metabolites were determined by 1D, 2D NMR spectroscopic data and HRESIMS data analysis. The compounds have shown moderate-to-high antimicrobial activities. The structure and the relative stereochemistry of the metabolite 1 have been determined by X-ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Soft corals, in particular, those belonging to the genus Sinularia, have proven to be rich sources of bioactive norcembranoids. Previous bioassay results of these macrocyclic metabolites demonstrated cytotoxic, , antifungal, antiviral, and anti-inflammatory activities. ,, Furthermore, some cembranoids , and steroids , with attractive bioactivities have also been discovered from corals of this genus. A literature search showed that previous chemical investigations of the soft coral Sinularia erecta (Klunzinger, 1877) afforded only a limited number of sesquiterpenes, cembranoids, and 18-norcembranoids, and until now, the biological activities of these compounds have not been investigated.…”
mentioning
confidence: 99%
“…Soft corals, in particular, those belonging to the genus Sinularia, have proven to be rich sources of bioactive norcembranoids. Previous bioassay results of these macrocyclic metabolites demonstrated cytotoxic, , antifungal, antiviral, and anti-inflammatory activities. ,, Furthermore, some cembranoids , and steroids , with attractive bioactivities have also been discovered from corals of this genus. A literature search showed that previous chemical investigations of the soft coral Sinularia erecta (Klunzinger, 1877) afforded only a limited number of sesquiterpenes, cembranoids, and 18-norcembranoids, and until now, the biological activities of these compounds have not been investigated.…”
mentioning
confidence: 99%
“…Marine life is ripe of organisms that have specialized to survive by developing strategies which involve production of certain secondary metabolites that are not common in terrestrial life. In view of this, we are interested to distract those compounds from marine life forms which could be of medicinal importance, see also [1]. Here, we present the spectroscopic characterization of a compound from the ethyl acetate extract of the sponge Ircinia sp.…”
mentioning
confidence: 99%